Writing centers, libraries, and medical and pharmacy schools - Melanie J. McGurr (Journal of the Medical Library Association, 2020)
Objective: This study investigated the existence of writing centers at medical and pharmacy schools, the location of those writing centers in a library or elsewhere, and librarians’ perceptions of how writing centers are viewed by students, faculty, and staff. Methods: A twelve-question survey was sent to libraries affiliated with a medical and pharmacy school in the United States. Results: Respondents were curious about writing centers, how they were viewed on campus, and how to start one. Overall, respondents described engagement with writing centers: 68% had a writing center on campus, 23% had a writing center in their library, and 11% had a writing center on the health sciences campus, including in the health sciences library. No respondents reported hearing negative comments from faculty or students about the writing centers, and 60% of respondents with writing centers that were available to medical and pharmacy students would recommend one to health sciences libraries without access to a writing center. Conclusion: This exploratory study showed that the establishment of writing centers in health sciences libraries is a topic of interest. Future studies could further investigate health sciences libraries’ roles in writing centers for pharmacy, medical, and other health sciences students.